GENETIC VARIABILITY AND CORRELATION IN EXOTIC CUCUMBER (Cucumis sativus L.) VARIETIES - Ullah, M. Z.; Hasan, M. J.; Chowdhury, A. Z. M. K. A.; Saki, A. I.; Rahman, A. H. M. A. (Bangladesh Journal of Plant Breeding and Genetics, 2012)
Twelve exotic cultivars of cucumber (Cucumis sativus) were grown to assess the presence of variability for desired traits and amount of variation for different parameters. Genetic parameters, correlations, partial correlation and regressions were estimated for all the traits. Analysis of variance revealed significant differences among entries for all the characters. The estimates of genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were high for yield per plant, fruits per plant, fruit weight and fruit length. Broad sense heritability estimates for various traits ranged from 42.26 to 89.55%. Fruit yield per plant showed high significant positive correlation with fruits per plant, fruit weight, flesh thickness, fruit diameter and leaves per plant. Partial correlation was significant for fruits per plant and indicated these traits contributed over 70% to total fruit yield. By variability, correlation and regression analysis it was concluded that more fruits per plant and more fruit weight are major yield contributing factors in selecting high yielding cucumber cultivars. DOI: http://dx.doi.org/10.3329/bjpbg.v25i1.17008